2017
DOI: 10.1002/2016jc012507
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of coral reefs by combining lidar and MBES data: A case study from Yuanzhi Island, South China Sea

Abstract: The correlation between seafloor morphological features and biological complexity has been identified in numerous recent studies. This research focused on the potential for accurate characterization of coral reefs based on high‐resolution bathymetry from multiple sources. A standard deviation (STD) based method for quantitatively characterizing terrain complexity was developed that includes robust estimation to correct for irregular bathymetry and a calibration for the depth‐dependent variablity of measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The bathymetric data were mainly collected in May 2016 by a high-resolution shallow-water MBES, R2SONIC 2024, and processed by the CARIS HISP/SISP 9.1 package [21]. The swath sector in real time for R2SONIC 2024 is 10°-160°, and its frequency ranges from 200 to 400 kHz.…”
Section: Study Sites and Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The bathymetric data were mainly collected in May 2016 by a high-resolution shallow-water MBES, R2SONIC 2024, and processed by the CARIS HISP/SISP 9.1 package [21]. The swath sector in real time for R2SONIC 2024 is 10°-160°, and its frequency ranges from 200 to 400 kHz.…”
Section: Study Sites and Experimental Datamentioning
confidence: 99%
“…Wang et al [20] merged multibeam backscatter and airborne LiDAR data and found that joint classification achieved comparatively higher accuracies than single-source classification, although accuracy evaluation was conducted in only a small part of the study area. Zhang et al [21] investigated the terrain complexity parameter and mapped seabed coral abundance using LiDAR and multibeam bathymetry data without considering classification accuracy. Presently, benthic surveying of the seafloor via the combination of acoustics and optics is still in its infancy, as evidenced by the few relevant experiments and insufficient accuracy assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Fish tend to prefer strong upwelling regions (Cai et al, 2021), and Hainan accounts for 0.1% of all ocean upwelling regions worldwide (Ryther, 1969). The recent surge in coastal urbanization on Hainan Island has seen an increase in wastewater discharge, agricultural development, and human activities, which have polluted Hainan Island to a serious degree (Li et al, 2014;Xu et al, 2018;Zhang et al, 2017). These increases are expected to worsen the contamination of marine sediments, which will have a direct negative impact on aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the presented method provided better characterization of seafloor terrain complexity. Meanwhile, the obtained surface roughness (SR) index was found to be significantly correlated with in situ coral abundance observations, which suggested that the SR index was a suitable indicator of habitat complexity in a coral reef environment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%